Arterial and Venous Thromboembolic Complications in 832 Patients with BCR-ABL-Negative Myeloproliferative Neoplasms - Wille, Kai; Deventer, Eva; Sadjadian, Parvis; Becker, Tatjana; Kolatzki, Vera; Hünerbein, Karlo; Meixner, Raphael; Jiménez-Muñoz, Marina; Fuchs, Christiane; Griesshammer, Martin (Hämostaseologie, 2023)
Arterial (ATE) and venous (VTE) thromboembolic complications are common causes of morbidity and mortality in BCR-ABL-negative myeloproliferative neoplasms (MPNs). However, there are few studies that include all MPN subtypes and focus on both MPN-associated ATE and VTE. In our single-center retrospective study of 832 MPN patients, a total of 180 first thromboembolic events occurred during a median follow-up of 6.6 years (range: 0–37.6 years), of which 105 were VTE and 75 were ATE. The probability of a vascular event at the end of the follow-up period was 36.2%, and the incidence rate for all first ATE/VTE was 2.43% patient/year. The most frequent VTE localizations were deep vein thrombosis with or without pulmonary embolism (incidence rate: 0.59% patient/year), while strokes were the most frequent ATE with an incidence rate of 0.32% patient/year. When comparing the group of patients with ATE/VTE (n = 180) and the group without such an event (n = 652) using multivariate Cox regression analyses, patients with polycythemia vera (hazard ratio [HR]: 1.660; [95% confidence interval [CI] 1.206, 2.286]) had a significantly higher risk of a thromboembolic event than the other MPN subtypes. In contrast, patients with a CALR mutation had a significantly lower risk of thromboembolism compared with JAK2-mutated MPN patients (HR: 0.346; [95% CI: 0.172, 0.699]). In summary, a high incidence of MPN-associated VTE and ATE was observed in our retrospective study. While PV patients or generally JAK2-mutated MPN patients had a significantly increased risk of such vascular events, this risk was reduced in CALR-mutated MPN patients.
Keywords: arterial thrombosis; deep vein thrombosis; management of disease; venous thrombosis